Soft Skills and Creative Activity: Analysis of Interconnection in the Education of Future Graphic Design Professionals - Kateryna Vitchynkina (Educational Challenges)
The purpose is to conduct a comprehensive analysis of the correlation between soft skills and indicators of creative activity among future graphic design professionals, utilizing methods of theoretical analysis of educational standards. The relevance of this research is determined by the necessity to develop soft skills and creative activity in future professionals in graphic design within the framework of the contemporary job market.